ISLAMISM IN MADURA: From Religious Symbolism to Authoritarianism (State Islamic University (UIN) of Sunan Ampel Surabaya, 2018)
The article scrutinizes the role and action of a number of Muslim organizations established by some prominent kiais in Pamekasan Madura, namely Badan Silaturrahmi Ulama Pesantren Madura (BASSRA/The Board of Madurese Pesantren Ulama), Aliansi Ulama Madura (AUMA/The Alliance of Madurese Ulama), and Forum Kiai Muda (FKM/The Forum of Young Kiais). These organizations, on the basis of their religious thoughts and movements, have been able to massively mobilize and organize their followers while at the same time create a multi-layered sectarianism. The sectarianism promulgated by these organizations seems to disrespectfully neglect interreligious and interethnic relations which rest within heterogeneous reality of the Madurese society. Consequently, the domination of the religious elites seems to “lock” the freedom of thought in religion. This article argues that Islamism in Pamekasan—as a variant of Islam in response to the global phenomena on religious fundamentalism—has uniquely focused on what so-called “nationalization of Islam”. It implies that the Islamist groups in Pamekasan attempt to mobilize their followers, on behalf of Islam, in order to not only establish an Islamic state but also to renovate Indonesia.